2003
DOI: 10.1364/ao.42.002415
|View full text |Cite
|
Sign up to set email alerts
|

W/SiC x-ray multilayers optimized for use above 100 keV

Abstract: We have developed a new depth-graded multilayer system comprising W and SiC layers, suitable for use as hard x-ray reflective coatings operating in the energy range 100 -200 keV. Grazing-incidence x-ray reflectance at E ϭ 8 keV was used to characterize the interface widths, as well as the temporal and thermal stability in both periodic and depth-graded W͞SiC structures, whereas synchrotron radiation was used to measure the hard x-ray reflectance of a depth-graded multilayer designed specifically for use in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 8 publications
(1 reference statement)
2
24
0
Order By: Relevance
“…Previously we measured the reflectance of prototype hard X-ray W/Si and W/SiC multilayers designed for use above 100 keV; we found that the measured reflectance did not agree well with calculations of the expected performance made using optical constants determined from theoretical atomic scattering factors and mass absorption coefficients. We were able to get better agreement however with calculations made using experimentally derived optical constants measured over the energy range E = 120 -180 keV, which we determined for W and SiC, as well as for Ni .93 V .07 and B 4 C. 6 The discrepancy between the measured and theoretical optical constants can be partly attributed to incoherent (Compton) scattering, which is a particular concern especially for lighter elements at these energies, and which might not be properly accounted for in the available scattering factors and mass absorption coefficients.…”
Section: Introductionsupporting
confidence: 72%
“…Previously we measured the reflectance of prototype hard X-ray W/Si and W/SiC multilayers designed for use above 100 keV; we found that the measured reflectance did not agree well with calculations of the expected performance made using optical constants determined from theoretical atomic scattering factors and mass absorption coefficients. We were able to get better agreement however with calculations made using experimentally derived optical constants measured over the energy range E = 120 -180 keV, which we determined for W and SiC, as well as for Ni .93 V .07 and B 4 C. 6 The discrepancy between the measured and theoretical optical constants can be partly attributed to incoherent (Compton) scattering, which is a particular concern especially for lighter elements at these energies, and which might not be properly accounted for in the available scattering factors and mass absorption coefficients.…”
Section: Introductionsupporting
confidence: 72%
“…The -in terms of imaging -ideal gamma-ray imager, a gamma-ray lens, is very difficult to realize due to the small angle of total reflection for gamma rays. Multilayer, diffractive optics systems have been built which are able to focus gamma rays up to 160 keV, however, these systems are characterized by a large focal length and very small field-of-view [9]. The FOV is typically less than 1 deg.…”
Section: Overview Of Gamma-ray Imaging Conceptsmentioning
confidence: 99%
“…A multilayer structure consists of thin layers of alternating elements or compounds. [6,7] These multilayer materials offer unique structural, [8] magnetic [9,10] and electronic [11,12] properties for a wide range of applications. A multilayer structure such as an X-ray optical element is used in many technological applications like in X-ray astronomy, microscopy, spectroscopy, and as filters and monochromators for synchrotron radiation and free electron X-ray lasers.…”
Section: Introductionmentioning
confidence: 99%